(untitled) (Research, Society and Development, 2021)
This article promotes the need to overcome the dichotomy between human action and God’s action. The question is: how to promote the spirit of love, unity and fraternal life? The method is narrative-bibliographic, and the objective is to overcome the dichotomy and assume the unity of love is to recognize that the human being, created from the humus of the earth to the sound of God’s voice, is able to feel the needs and possibilities, at the same time, able to hear the voice of the Spirit. The administrative essence is elucidated, which is praxis, fostering unity and human action in the narrative that human beings are administrators and co-creators of God’s work. Expecting the future is a possibility, it is a necessity, and it takes place in spousalty with the Creator. The formation of a person’s conscience is fundamental, so that it is possible, through human action, to manage God’s Creation.